2018
DOI: 10.1002/cphc.201701148
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of a Single Ag Nanoparticle Observed by Dark‐field Microspectroscopy

Abstract: Silver nanoparticles (AgNPs) have been widely used as photocatalysts and nanosensors. Observation of the spectroscopy of a single AgNP greatly helps us understand the catalytic characteristics and morphology change of the AgNP during reactions. In the present study, AgNPs physically adsorbed on indium tin oxide (ITO) conductive glass were electrochemically reduced and oxidized, and the plasmonic resonance Rayleigh scattering (PRRS) spectrum of an individual AgNP was observed under a dark-field microscopy (DFM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The first spin–orbit pair of small intensity at higher BE values is due to the oxidized Ag surface atoms bonding with the peptide molecule. The main signal, the Ag 3d 5/2 component, centered at 367.6 eV BE, corresponds to metallic Ag atoms in the bulk of AgNPs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first spin–orbit pair of small intensity at higher BE values is due to the oxidized Ag surface atoms bonding with the peptide molecule. The main signal, the Ag 3d 5/2 component, centered at 367.6 eV BE, corresponds to metallic Ag atoms in the bulk of AgNPs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of Ag-based metallic NPs into Ag + salt nanocrystals is evidenced under dark-field microscopy by a decrease in the intensity of the light they scatter without, however, reaching total signal extinction. A spectrometer inserted at the end of the optical path, or a hyperspectral camera, completed the pure optical imaging with their UV-vis spectrum, providing information on the composition and conversion mechanisms in solutions of Ag + precipitating agents (77,78,(86)(87)(88).…”
Section: Electrochemical Conversionmentioning
confidence: 99%
“…(B) Schematic of the structural change of silver nanoparticles monitored by DFM. Adapted from Pang, J.; Liu, H.-L.; Li, J.; Zhai, T.-T.; Wang, K.; Xia, X.-H. ChemPhysChem 2018 , 19 , 954–958 (ref ). Copyright 2018 Wiley.…”
Section: Accurate Analysis Applicationmentioning
confidence: 99%
“…It was determined that the electrochemical detection of silver nanoparticles could be inhibited at the electrode surface at high electrode potentials . During the iDFM of the electrochemical redox of silver nanoparticles, Wang et al discovered that electrochemical reduction could not completely lead to recovery of the wavelength shift after electrochemical oxidization, which was attributed to the newly formed small silver nanoparticles (Figure B) . Tschulik and co-workers also investigated the electrochemical dissolution of silver nanoparticles in different systems with hyperspectral DFM and found that the dissolution process could be regulated by the coexisting anions. , …”
Section: Accurate Analysis Applicationmentioning
confidence: 99%
See 1 more Smart Citation